2020
DOI: 10.7150/jca.39033
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Esophageal Fistula after Radiotherapy for Esophageal Squamous Cell Carcinoma

Abstract: Purpose: The aim of this study was to investigate risk factors for esophageal squamous cell carcinoma (ESCC) treated with radiotherapy (RT) with or without chemotherapy to guide how to reduce the occurrence of esophageal fistula (EF). Methods: 414 patients with ESCC who underwent RT with or without chemotherapy were collected in Shandong Cancer Hospital from February 2012 to June 2018 retrospectively. The clinical characters and dosimetric parameters were recorded. Univariate and multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
3
22
1
Order By: Relevance
“…It was proved that T stage was a signi cant risk factor for stula in accordance with previous results [24] , which had a certain relationship with wall thickness in esophageal SCC. Another mentioned risk factors were deep ulcer presence and ulcer-to-tumor ratio in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was proved that T stage was a signi cant risk factor for stula in accordance with previous results [24] , which had a certain relationship with wall thickness in esophageal SCC. Another mentioned risk factors were deep ulcer presence and ulcer-to-tumor ratio in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Another study by Tsushima et al [14] demonstrated that 89% of patients with esophageal stula presented ulcerative esophageal carcinoma. Hu et al [24] indicated that ulcerative esophageal cancer was associated with esophageal stula. The advantage of this study was that quantitative CT analysis assessing deep ulcers was more accurate in predicting esophageal stula.…”
Section: Discussionmentioning
confidence: 99%
“…In our multivariate analysis, tumors with ulcerations detected by endoscopy or barium esophagography was one of the two independent predictors of fistula development for T4b lesion. Of interest, the OR for fistula formation was 2.206 (95% CI: 1.188-4.094) among esophageal carcinoma patients with esophageal ulceration in a cohort of 414 ESCC patients when compared to those without ulceration [22]. Similarly, other studies also reported ulcerative-type cancer among cases of ESCC with fistula ranging from 64.7% [23] to 89% [18].…”
Section: Discussionmentioning
confidence: 84%
“…T4 stage and ulcerative ESCC were risk factors associated with esophageal fistula. 32 , 33 High esophageal fistula rates of 22% (31/140), 34 24% (28/116) 35 and 30.1% (41/136) 36 were reported in patients with ESCC and receiving definitive chemoradiotherapy, which accounted for 76%, 34 100% 35 and 100% 36 in all patients with T4 or T4b tumors, individually. Relative low rate of 10.38% (22/212) was also reported in ESCC patients who received definitive chemoradiotherapy, which accounted for 15.09% in T4 patients.…”
Section: Discussionmentioning
confidence: 99%